Preventing bisphosphonate induced osteonecrosis of the jaw with a polyguanidine conjugate (GuaDex): a promising new approach - Cantorán Castillo, Arquímedes; Beltrán Salinas, Belinda; Antúnez Treviño, Jorge M.; Martínez Pedraza, Ricardo; Franco Márquez, Rodolfo; Guzmán García, Mario A.; Cerda Flores, Ricardo Martín; Perales Pérez, Raúl Vicente; Zakian, Christian; Ancer Rodríguez, Jesús; Márquez Méndez, Marcela (Elsevier, 2024)
Osteonecrosis of the jaw (ONJ) is a relatively rare side effect after prolonged use of bisphosphonates, which are drugs used to treat bone resorption in osteoporosis and certain cancers. This study introduces a novel ONJ model in rats by combining exposure to bisphosphonates, oral surgery, and bacterial inoculation. Potential ONJ preventive effects of polyguanidine (GuaDex) or antibiotics were evaluated. The study consisted of twenty-four male Wistar rats were divided into four groups. Groups 1 to 3 were given weekly doses of i.v. Zoledronic acid (ZA), four weeks before and two weeks after an osteotomy procedure on their left mandibular first molar. Group 4 was a negative control. Streptococcus gordonii bacteria were introduced into the osteotomy pulp chamber and via the food for seven days. On day eight, the rats were given different treatments. Group 1 was given a GuaDex injection into the osteotomy socket, Group 2 was given an intramuscular (i.m.) injection of clindamycin, Group 3 (positive control) was given an i.m. injection of saline, and Group 4 was given an i.m. injection of saline. Blood samples were taken two weeks after the osteotomy procedure, after which the rats were euthanized. Bone healing, bone mineral density, histology, and blood status were analyzed. The results showed that Group 1 (GuaDex) had no ONJ, extensive ongoing bone regeneration, active healing activity, vascularization, and no presence of bacteria. Group 2 (clindamycin) showed early stages of ONJ, avascular areas, and bacteria. Group 3 showed stages of ONJ, inflammatory infiltrates, defective healing, and bacterial presence, and Group 4 had normal healing activity and no bacterial presence. Conclusion: ZA treatment and bacterial inoculation after tooth extraction inhibited bone remodeling/healing and induced ONJ characteristic lesions in the rats. Only GuaDex apparently prevented ONJ development, stimulated bone remodeling, and provided an antimicrobial effect.